Methodological issues on 'challenges and opportunities towards the road of universal health coverage (UHC) in Nepal: a systematic review' - Chhabi Lal Ranabhat; Devaraj Acharya (BMC, 2020)
Abstract Challenges and opportunities towards the road of universal health coverage (UHC) in Nepal: a systematic review' is a policy review paper and we published in BMC - Archives of Public Health. Policy research is the process of conducting research, analysis of, a fundamental social problem in order to provide policymakers with pragmatic, action-oriented recommendations for alleviating the problem. The objective of this paper is to illustrate some methodological issues used in that paper.